The impact of the strategy of the six hats in teaching science on the development of creative thinking for secondary school students in the schools of Ma’an in Jordan - Al-Shalabi, Najwa Mohammed (Journal of Educational and Psychological Sciences, 2019)
This study aimed at uncovering the impact of the strategy of the six hats in the teaching of science on the development of creative thinking among second grade students (in the schools of Jordan Ma’an governorate). The sample of the study consisted of (50) students from the second grade students, and distributed to two divisions (A and B). One of the two groups was randomly chosen to be the control group (25). The other division represented the experimental group (25) students. In the tribal and remote measures, the creative thinking test was used as the image of the words "A", according to the training program prepared by the researcher. The results showed that there were statistically significant differences in the performance of the study subjects on the test of creative thinking as a whole, and its three dimensions (fluency, flexibility, and originality), And its three dimensions (fluency, flexibility, and originality) were attributed to the six hats program and the academic average for the experimental group, while there were no statistically significant differences in the performance of the study subjects and its secondary dimensions due to the interaction between the training program and the academic rate. In the light of the results reached, the researcher recommended conducting further studies using the program on basic and intermediate grades in other regions to verify its effectiveness. Because it has a positive impact in the development of creative thinking.